Blended Learning in a Traditional EFL Environment: Students’ perception and Teachers’ attitude - Kasapis, Constantinos (Language Center, Cyprus University of Technology, 2021)
This action research (AR) study was conducted with the purpose of gaining an insight in Blended Learning (BL) and its efficiency to improve English as a Foreign Language (EFL) students' performance in a rather traditional language classroom setting. More specifically, the study aims at investigating the students’ perceptions of the effectiveness of BL, and any contribution of it to the improvement of their writing skills. At the same time an effort was made to investigate and identify teachers' attitude towards blended instruction and the use of technology in their teaching methods. Forty-five teachers answered a questionnaire and five EFL teachers of the same study population were interviewed. The results showed that the vast majority of the teachers had never used BL in their instruction due to the absence of training or the lack of expertise. During the implementation of the AR, thirty students were selected to participate in the one-semester study. An embedded design was applied to investigate students’ perception of the blended approach. Both quantitative and qualitative data showed a positive impact on students' perception about the effectiveness of BL in a traditional language learning environment. The findings also revealed a positive perception of students to work in such an environment and their readiness and keenness for an alternative method of learning. Finally, a paired sample T-test was computed to showcase the impact of BL on student achievement comparing their exam results before and after the intervention, which showed a statistically significant difference. The results should be carefully evaluated before adopting this BL model since so little research has been conducted on this specific venture in Cyprus Secondary Education so far. Further research should be conducted with a view to comparing the results and drawing safer conclusions.
Keywords: Blended learning; English as a Foreign Language (EFL); Students’ perceptions